2016
DOI: 10.1055/s-0042-100292
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-intensity Intermittent and Moderate-intensity Continuous Exercise on Autonomic Modulation in Young Men

Abstract: The aim of this study was to compare heart rate variability (HRV) recovery after two iso-volume (5 km) exercises performed at different intensities. 14 subjects volunteered (25.17±5.08 years; 74.7±6.28 kg; 175±0.05 cm; 59.56±5.15 mL·kg(-1)·min(-1)) and after determination of peak oxygen uptake (VO2Peak) and the speed associated with VO2Peak (sVO2Peak), the subjects completed 2 random experimental trials: high-intensity exercise (HIE - 1:1 at 100% sVO2Peak), and moderate-intensity continuous exercise (MIE - 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…This is supported by the group effect between HIIE recovery was delayed for 25 and 30 min after HIIE 1.25 and HIIE 2.5 , respectively. On the other hand, Cabral-Santos et al [8] observed that LF-log returned to rest level after 20 min of recovery after a 5-km HIIE, whereas HF-log remained elevated for 35 min. The results observed in the present study show that the volume of high-intensity exercise training protocols also affect HRV recovery.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is supported by the group effect between HIIE recovery was delayed for 25 and 30 min after HIIE 1.25 and HIIE 2.5 , respectively. On the other hand, Cabral-Santos et al [8] observed that LF-log returned to rest level after 20 min of recovery after a 5-km HIIE, whereas HF-log remained elevated for 35 min. The results observed in the present study show that the volume of high-intensity exercise training protocols also affect HRV recovery.…”
Section: Discussionmentioning
confidence: 93%
“…During recovery, HRV is kept low for a few minutes according to exercise intensity, duration, and mode [9,25,33]. HRV recovery is widely used to determine acute stress response to different modes of exercise in both trained and untrained individuals [4,8,33]. This information is relevant for exercise prescription, and because HIIE has become widely used for different populations, understanding the stress responses of the autonomic nervous system after HIIE of similar intensities but different volumes is important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this, researches show that regular practice of physical activity leads the individual to have a more pronounced HR recovery when comparing the same indexes in the weeks before sedentary people beginning the practice. In this way, there is a greater physical resistance, decreasing the ability to overload the heart in other activities 21,22 .…”
Section: Discussionmentioning
confidence: 99%